2009
DOI: 10.1186/1471-230x-9-44
|View full text |Cite
|
Sign up to set email alerts
|

Gluten sensitivity enteropathy in patients with recurrent aphthous stomatitis

Abstract: BackgroundGluten sensitive enteropathy (GSE) is an autoimmune enteropathy triggered by the ingestion of gluten-containing grains in susceptible individuals. Recurrent aphthous stomatitis (RAS) may be the sole manifestation of GSE. The aim of this study was to determine the prevalence of gluten sensitivity enteropathy (GSE) in a large group of patients with RAS and assess the efficacy of gluten free diet (GFD) on the improvement of aphthous lesions in those who were diagnosed with GSE.MethodsTwo hundred and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
(26 reference statements)
0
16
3
4
Order By: Relevance
“…It was reported that CD patients with RAS showed a significant improvement in their aphthous lesions after GFD [8,17,27]. On the other hand, Hunter et al [28] examined the effects of GFD in patients with RAS and without CD and found no statistical significance between the study group with GFD and the control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that CD patients with RAS showed a significant improvement in their aphthous lesions after GFD [8,17,27]. On the other hand, Hunter et al [28] examined the effects of GFD in patients with RAS and without CD and found no statistical significance between the study group with GFD and the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic, immunological and microbial factors may play a role in the occurrence of RAS. Also local trauma, stress, food intake, some drugs, hormonal changes or vitamin and trace element deficiencies could play a role [27]. However, some studies reported nonsignificant differences in RAS in CD patients versus controls [8,16].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent aphthous ulcers occur more commonly in patients with celiac disease in some series [162,164] but not all [166]. The frequency of celiac disease in those with recurrent ulcers may be higher that in the general population with a threefold increase, but small bowel histological changes may be mild [167]. When ulcers are present, a gluten-free diet is an effective cure [168].…”
Section: Other Gastrointestinal Disordersmentioning
confidence: 97%
“…The researchers concluded that patients who were unresponsive to RAS treatments should always be investigated for gluten intolerance. 7 Furthermore, there are many cases of subclinical celiac disease in patients whose RAS is reduced when a glutenfree diet is adopted. In addition, both confirmed and subclinical/silent celiac disease are increasing in incidence.…”
Section: Food Sensitivitiesmentioning
confidence: 99%